2002
DOI: 10.1016/s1468-6996(02)00005-0
|View full text |Cite
|
Sign up to set email alerts
|

High temperature strength, fracture toughness and oxidation resistance of Nb–Si–Al–Ti multiphase alloys

Abstract: Nb±Si±Al±Ti quaternary phase diagram around three-phase region, which consists of niobium solid solution (Nb ss), Nb 3 Al and Nb 5 Si 3 , is constructed in this study. The three-phase region exists up to titanium content of about 20 mol%. Based on the quaternary phase diagram, three-phase alloys containing Nb ss from about 50 to 75% in volume are prepared to improve high temperature strength, room temperature fracture toughness and oxidation resistance simultaneously. When microstructure and composition are op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(21 citation statements)
references
References 20 publications
(36 reference statements)
2
16
0
1
Order By: Relevance
“…The diffusion distances of the alloying elements are estimated to be less than 500 nm, so that morphologies and compositions of the former BCC1, BCC2, and Laves phases retain while oxidation of these phases is accompanied by large volume expansion. This behavior is somewhat different from the oxidation behavior of conventional Nb alloys, as well as developmental Nb-Si-Al-Ti alloys, where a preferable metal oxide scale forms resulting in a decrease in the concentration of the alloying elements inside the Nb matrix, an increase in the oxygen solubility and eventually internal oxidation [15,28]. Reduced diffusion rates of the alloying elements in high-entropy alloys were noted in previous publications [6,12,13] and it was attributed to a reduced concentration of free vacancies in these multiprincipal-element alloys.…”
Section: Oxidation Reactionsmentioning
confidence: 83%
See 1 more Smart Citation
“…The diffusion distances of the alloying elements are estimated to be less than 500 nm, so that morphologies and compositions of the former BCC1, BCC2, and Laves phases retain while oxidation of these phases is accompanied by large volume expansion. This behavior is somewhat different from the oxidation behavior of conventional Nb alloys, as well as developmental Nb-Si-Al-Ti alloys, where a preferable metal oxide scale forms resulting in a decrease in the concentration of the alloying elements inside the Nb matrix, an increase in the oxygen solubility and eventually internal oxidation [15,28]. Reduced diffusion rates of the alloying elements in high-entropy alloys were noted in previous publications [6,12,13] and it was attributed to a reduced concentration of free vacancies in these multiprincipal-element alloys.…”
Section: Oxidation Reactionsmentioning
confidence: 83%
“…Without protective coating, oxidation of these alloys occurs very rapidly, with considerable weight gain, which generally exceeds 0.04 mg/cm 2 /s (150 mg/ cm 2 /h), followed by alloy embrittlement and disintegration. Several developmental Nb alloys with improved oxidation resistance, containing Ti, Si, Al, and some other elements, have recently been reported [27][28][29]. Unfortunately, these developmental alloys contain high volume fractions of silicides and aluminides and are brittle at temperatures less than *1000 K. The results of isothermal oxidation at 1273 K of these developmental alloys are given in Table 6.…”
Section: Oxidation Kineticsmentioning
confidence: 99%
“…The formation of A15-Nb 3 Al in Nb silicide based alloys is possible depending on the Ti/Al ratio in the alloy [14].…”
Section: Introductionmentioning
confidence: 99%
“…In order to achieve a balance among properties of good creep strength, excellent oxidation resistance and acceptable fracture resistance, the volume fraction and the morphology of each constituent phase must be controlled reasonably. It was found that addition of a higher content of Cr improved the high temperature oxidation resistance due to formation of the Laves phase [4][5][6][7][8] , so the new Nb-Ti-Cr-Si based alloys have attracted ever increasing attentions. Their phase constituents are Nb solid solution (Nbss), (Nb,X)5Si3(X represents Ti,Hf and Cr elements) and Cr2Nb.…”
Section: Introductionmentioning
confidence: 99%